2011
DOI: 10.1530/eje-11-0447
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism as a risk factor for cardiovascular mortality in men: a meta-analytic study

Abstract: Objective: To verify whether hypogonadism represents a risk factor for cardiovascular (CV) morbidity and mortality and to verify whether testosterone replacement therapy (TRT) improves CV parameters in subjects with known CV diseases (CVDs). Design: Meta-analysis. Methods: An extensive Medline search was performed using the following words 'testosterone, CVD, and males'. The search was restricted to data from January 1, 1969, up to January 1, 2011. Results: Of the 1178 retrieved articles, 70 were included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
258
2
12

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(292 citation statements)
references
References 113 publications
12
258
2
12
Order By: Relevance
“…There is an inverse relationship between endogenous serum testosterone levels and coronary heart disease in males (8,11,12) although all studies cannot confirm this finding (6,13,14,15,16), and the direction of causality of the phenomenon remains unclear. Moreover, a decreased serum testosterone concentration has been shown to be associated with acute ischemic strokes, infarct size and mortality (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 96%
See 1 more Smart Citation
“…There is an inverse relationship between endogenous serum testosterone levels and coronary heart disease in males (8,11,12) although all studies cannot confirm this finding (6,13,14,15,16), and the direction of causality of the phenomenon remains unclear. Moreover, a decreased serum testosterone concentration has been shown to be associated with acute ischemic strokes, infarct size and mortality (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 96%
“…In patients with a previous history of cardiovascular disease (CVD) events, hypogonadism has been reported to associate with a reduced risk of new CVD events (6). On the other hand, low serum testosterone concentration has also been proposed to predict increased cardiovascular risk (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…The relative risk for an increase of one standard deviation of testosterone was 0.84 (95% CI 0.76 to 0.92). Another meta-analysis confirmed the association of low testosterone with mortality, but failed to demonstrate a significant association with incident CV disease (22). The point estimate suggested increased CV disease incidence with lower testosterone, but the 95% CI included no effect.…”
Section: Endogenous Testosterone In Older Menmentioning
confidence: 98%
“…Accordingly, the presence of hypogonadism in men with cardiovascular disease (CVD) is about two times higher than observed in the general population and is associated with increase of the most known cardiovascular risk factors, and cardiovascular morbidity and mortality [1]. The most recent studies have also identified that men with CVD show significantly lower serum levels of bioavailable T than those men with negative coronary angiography (see Box 1 for CV safety issues and T-replacement).…”
Section: Background On Testosteronementioning
confidence: 99%